Psychological effects of Anfal on Kurdish women's personalities - Muhammad, Dr. Mariwan Abdul Majid Muhammad; Sadruddin, Kazem Ahmed Sadruddin (Sulaimani Journal for Humanities, 2026)
The Anfal campaign, also known as the Kurdish Genocide, Operation Anfal was a genocide against the Kurdish people to describe the carefully planned and orchestrated eight-staged genocidal campaign between February 23rd and September 6th 1988. The role of women survivors of Anfal in Kurdish society, especially after the Anfal disaster were significant, this because most of the women have a big responsibility, such as looking at after their children and working outside of home, despite the difficulties and Kurdish social traditions, women together with men worked hard outside the home as laborers in order to help their children and building society. This research is based on two main aspects: theory and the practice. The aim of this study was to investigate the symptoms of anxiety, depression, stress, insomnia and inferiority feeling among women survivors of anfal campaign in terms of age, socioeconomic status in Kurdistan Region. This study used SPSS-26 to analyse data and conducted that ADSIIS-35 has a good reliability. The researcher used the quantitative questionnaire to collect data. In total 200 women survivors were invited to participate in this study, but only 150 participants filled in the questionnaire. The results showed a statistically significant correlations among stress, and insomnia and feeling of inferiority, and also there were a significant differences among the five sub-dimensions psychological problems according to age, socioeconomic status, university. At the end of this research, the results of the study were discussed, and there were some suggestions and recommendations to government and further researchers on women survivors of Kurdish Genocide.
Keywords: Anfal; Anfal campaign; Kurdish womens survivors; the psychological impacts of Anfal